2014
DOI: 10.1007/s13280-014-0555-2
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the social valuation of ecosystem services

Abstract: Methods to assess ecosystem services using ecological or economic approaches are considerably better defined than methods for the social approach. To identify why the social approach remains unclear, we reviewed current trends in the literature. We found two main reasons: (i) the cultural ecosystem services are usually used to represent the whole social approach, and (ii) the economic valuation based on social preferences is typically included in the social approach. Next, we proposed a framework for the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 50 publications
2
36
0
2
Order By: Relevance
“…While pollution and the forestry industry have a more prolonged effect, events such as earthquakes and tsunamis have a shorter duration, making it possible that people with a long history in the location understand that these disturbances occur at certain time intervals and that measures to address them must be developed [13]. This assessment of the perceptions of drivers of loss could be used to manage actions related to conservation, preservation, and the restoration of the system [61] by considering that the opinion of the population is a fundamental element in the current territorial management instruments.…”
Section: Discussionmentioning
confidence: 99%
“…While pollution and the forestry industry have a more prolonged effect, events such as earthquakes and tsunamis have a shorter duration, making it possible that people with a long history in the location understand that these disturbances occur at certain time intervals and that measures to address them must be developed [13]. This assessment of the perceptions of drivers of loss could be used to manage actions related to conservation, preservation, and the restoration of the system [61] by considering that the opinion of the population is a fundamental element in the current territorial management instruments.…”
Section: Discussionmentioning
confidence: 99%
“…In a review on the social evaluation of ESS, Felipe-Lucia et al (2015) [64] found that 22.9% of the reviewed studies focused on preference rankings for ESS, while only 7.2% provided a comparison between the present and future provision of ESS. This study adds to the lacking numbers of ESAs for future scenarios and is the first to do so for rubber production systems.…”
Section: Weighting Methods and Ess Evaluationmentioning
confidence: 99%
“…Our study used a multidisciplinary approach to incorporate multiple different views in the weighting of ES to calculate the RAVES index. However, studies aiming at assessing RAVES to maximize social–ecological values could implement other tools to weight ES, such as performing interviews to a broader range of stakeholders (Felipe‐Lucia, Comín, & Escalera‐Reyes, ). For instance, previous work in our study area identified that ES are used and valued differently by each stakeholder group (Felipe‐Lucia, Martín‐López, et al., ).…”
Section: Discussionmentioning
confidence: 99%